Incidence and Outcomes of Cytomegalovirus (CMV) Infection among Hematopoietic Stem Cell Transplant (HSCT) Recipients. (4th October 2017) - Furuno, Jon P; Elman, Miriam R; Noble, Brie N; Strasfeld, Lynne; Tallman, Gregory B; McGregor, Jessina C
Abstract: Background: Outcomes of CMV infection among HSCT recipients likely vary by patient population and treatment modality. However, data on these outcomes have been reported by relatively few centers. Methods: This was a retrospective cohort study of allogenic HSCT recipients age ≥18 years at Oregon Health and Science University Hospital (OHSU) between 2010–2015. During the study period, OHSU standard practice was to preemptively treat CMV-viremic patients (quantitative PCR assay ≥ 200 copies/mL or consecutive PCR assays <200 copies/mL) with first-line valganciclovir or ganciclovir and second line foscarnet if there were contraindications to first-line agents. Study data were collected from an electronic health record repository and local Center for International Blood and Marrow Transplant Research (CIBMTR) database. Primary outcomes were clinical manifestations of CMV disease, death, and cause of death within 1 year of transplant. Results: Among 409 HSCT recipients, mean age was 53 (standard deviation: 13) years and 41% were female. 192 (47%) patients had CMV viremia and the median (interquartile range) time to CMV reactivation was 42 (31–53) days (Figure 1). Patients with acute myeloid leukemia were significantly less likely to have CMV reactivation (39% vs. 55%, P < 0.01) and those with myelodysplastic syndromes had a non-significantly higher risk (24% vs. 17%, P = 0.06). 4 (1%) patients had a documented clinical manifestation of CMV disease (3 pneumonia and 1 pancreatitis). One-year mortality was 36% (148/409); there was no significant difference in mortality (37.5% vs. 35.0%, P = 0.60) or cause of death ( P = 0.30) between patients with and without CMV reactivation (Figure 2). The most frequent causes of death among CMV viremic patients were recurrent/persistent disease (35%), acute graft vs. host disease (GVHD) (22%), infection (19%), and chronic GVHD (11%). CMV was documented as the primary cause of death for 2 patients. Conclusion: Nearly half of HSCT recipients had CMV reactivation and more than a third died within one year of transplant. However, incidence of CMV disease was rare and reactivation was not associated with increased mortality. Further study is needed to identify risk factors for CMV reactivation, infection and mortality in this population. Disclosures: J. P. Furuno, Merck & Co.: Consultant and Grant Investigator, Consulting fee, Research grant and Speaker honorarium. L. Strasfeld, Merck: Independent Contractor, Salary. J. C. McGregor, Merck & Co.: Grant Investigator, Research grant